SISTEM PENDIDIKAN UNTUK ANAK BERKEBUTUHAN KHUSUS DI SLB KARYA WINAYA PAMANUKAN - Nurfahira, Zahra; Darmiyanti, Astuti (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Chilldren as the natilon's next generatilon are a very ilmportant asset for the familly and the country. Chilldren are human resources that willl support the ILndonesilan natilon's journey iln the next few years. ILf currently chilldren's educatilon and development ils not carriled out optilmally, the development of the ILndonesilan natilon iln the next few years willl experilence dilffilcultiles. Artilcle 31 paragraph 1 of the 1945 Constiltutilon and Law Number 2 of 1989 concernilng the Natilonal Educatilon System, artilcle ILILIL paragraph, states that every ciltilzen has the same opportunilty to obtailn educatilon. SLB PGRIL Karya Wilnaya Pakarukan ilnvolves varilous aspects that must be explored iln more depth, IL want to know more about how the learnilng process at SLB PGRIL Karya Wilnaya Pakarukan takes ilnto account the dilversilty of students, so that researchers gailn knowledge about the applilcatilon of specilal needs educatilon to learnilng at SLB PGRIL Karya Wilnaya Uncle. Meanwhille, the object of the research ils the applilcatilon of learnilng for chilldren wilth specilal needs iln learnilng at SLB PGRIL Karya Wilnaya Pakarukan. The learnilng model at thils school ils assessment-based, where every new chilld who enters willl be assessed to determilne theilr specilfilc needs. Thils assessment ils carriled out to adjust teachilng methods, especilally for chilldren wilth hearilng ilmpailrments, both pure and multilple. Chilldren wilth pure hearilng ilmpailrments are usually able to follow lessons wilth certailn lilmiltatilons, whille chilldren wilth multilple ilmpailrments, such as hearilng ilmpailrments or mental ilmpailrments, requilre a more specilal approach. Thils research ailms to analyze the educatilon system for chilldren wilth specilal needs (ABK) and provilde recommendatilons for the repailr. Research filndilngs show that despilte silgnilfilcant efforts to ilmprove the ilnclusilve educatilon system, there are stilll challenges such as a lack of specilal trailnilng for teachers and adequate facilliltiles, as well as socilal stilgma that hilnders the success of ABK educatilon.